Face Recognition, NFC and Voice Controlled Door Lock System - Adalan, Kasim; Erkmen, Burcu (IEEE, 2016)
Door lock system was controlled with Face recognition, NFC and voice controlled as wireless communication by mobile application that is developed on Android operating system. By giving a voice command to Android phone and when Android phone is approached to NFC tag, door lock system was controlled. In addition, Face recognition process was used in this system. The face photo of a user was taken with camera on mobile phone running Android operating system. Human faces that was registered in database that was created for face recognition was compared with photo of the face that was taken by mobile phone, via face recognition algorithm. In this study, Bluetooth and NFC communication was used between mobile phone running Android operating system to electronic circuit board.
Keywords: Engineering